THE SPEECH ACTS OF REFUSING FOOD ON TELEVISION SERIES “TETANGGA MASA GITU?” - Farah Anjanillah (Department of English Literature, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
In having an interpersonal communication, the speaker might use numerous types of speech acts to convey his/her intended meaning due to a particular reason. Under the domain of pragmatics, the researcher was attracted to explore the use of speech acts for refusing food. Hence, this study aims to investigate the types of speech acts of refusing food performed by the characters on the TV series entitled “Tetangga Masa Gitu?” and uncover the aspects underlying the use of speech acts. In terms of approach, this inquiry applied a descriptive qualitative method. In undergoing the analysis, the researcher employed Austin’s (1962), Searle’s (1976), Wijana’s (1996) and Parker’s Riley’s (2014) notions on the speech acts types. To find out the aspects underlying the speech acts usage, the researcher implemented speech situation aspects and politeness maxims as proposed by Leech (1983) as well as Brown’s and Levinson’s politeness parameters (1987). The data were the utterances indicating the use of speech act to refuse food and the underlying aspects. The data were obtained through TV series “Tetangga Masa Gitu?”. The results exhibit that the characters used direct non-literal and indirect non-literal speech act to refuse food. Meanwhile, the aspects propelling the use of speech acts are politeness, distance, ranking of imposition (Brown Levinson, 1987) and culture (Leech, 1983).